THE ROLE OF PUPPET ART IN THE CREATION OF THE FOUNDATIONS OF THE THIRD RENAISSANCE - Islom Berdimurodov (Modern American Journals, 2025)
The role of the art of puppet theater in the further development of our national culture is significant. Only when the moral foundation of any independent state is strong can it be strong and develop widely. Today, the task of raising the younger generation to be morally and spiritually perfect is set by the state as a priority. The article presents an analytical opinion on the importance and role of the development of the art of puppet theater in our republic today.
Keywords: Theater, art, culture, youth, creativity, performance, puppet theater, ideological immunity.